BIBLIOMETRIC ANALYSIS OF AIR POLLUTION'S IMPACT ON CHILDREN WITH ASTHMA: INSIGHTS FROM A DECADE OF RESEARCH (2012-2022) - Ichtiarini Nurullita Santri; Lalu Muhammad Irham; Musfirah Musfirah; Yuniar Wardani; Khoiriyah Isni; Yohane Vincent Abero Phiri; Ahmad Faizal Rangkuti; Nopryan Ekadinata; Wirawan Adikusuma (The Indonesian Journal of Public Health, 2026)
Introduction: Asthma, a prevalent chronic inflammatory respiratory ailment, affects approximately 8% of children worldwide, with urban air pollution, particularly traffic-related pollutants, recognized as a significant contributor to its incidence. The heightened vulnerability of children due to their immature respiratory and immune systems accentuates the importance of addressing this issue. Aims: This study aims to explore the relationship between air pollution and children with asthma incidence and map the trends. Methods: We conducted a thorough bibliometric analysis, meticulously selecting 4,420 articles from the Scopus database based on specific inclusion criteria. These criteria included papers published between 2012 and 2022, with a particular emphasis on the keywords "air pollution," "asthma," and "children." Diverse bibliometric analyses, including performance analysis (citation analysis) and science mapping, were facilitated using specialized software. Keyword network construction and clustering analyses utilized data extracted from Bibtex, RIS, and CVS files with VOSviewer software. Results: The study uncovered 4,420 research documents, primarily categorized as "Research Article" (3,726 articles) and "Review Article" (618 articles), with the United States leading in citations (50,169), followed by China (13,187) and the United Kingdom (8,095). Conclusion: This bibliometric study delves into the intricate relationship between air pollution and children with asthma, illuminating extensive literature trends and influential countries. It enriches the understanding of children with asthma and informs future research aimed at mitigating air pollution's impact on this vulnerable population.